A Multidisciplinary Approach to the Management of inadequate clinical crown of Maxillary Central incisor: A Clinical Report - Maharjan, Shyam Kaji; Mathema, Suraj Ram Bhakta; Pradhan, Amina; Manipal, Supreet (Orthodontic Journal of Nepal, 2020)
Introduction: Anterior tooth fracture is the most commonly presenting clinical condition during routine dental practise. Restoration of such tooth is challenging task due to fracture position and amount of remaining coronal tooth structure. Tooth fracture at or below the gingival level usually have a poor prognosis. Treatment options for such clinical conditions range from tooth extraction to prosthodontic rehabilitation with surgical crown lengthening and/or orthodontic extrusion. This clinical report describes a multidisciplinary approach for management of such cases by the orthodontic forced eruption and clinical crown lengthening followed by the final restoration with indirect resin customized post core and crown.